A remarkable new genus of Iberian troglobitic Trechodina (Coleoptera: Carabidae: Trechinae: Trechini), with a revisited molecular phylogeny of the subtribe. Issue 2 (4th March 2021) - Faille, Arnaud; Balart-García, Pau; Fresneda, Javier; Bourdeau, Charles; Ribera, Ignacio
Summary: A new representative of the subtribe Trechodina, Iberotrechodes spinosus n. gen., n. sp ., subterranean and known so far from a single cave system of the Cantabrian chain (NW Spain), is described. The external morphology of the new species is highly derived within Trechodina, in particular for the peculiar and unique shape of its elytra, and likely due in part to its subterranean habits. A phylogenetic analysis based on six nuclear and mitochondrial genes placed it unambiguously within the subtribe Trechodina of Trechinae, as sister to all extent species of Trechodes plus Sporades, distributed in Africa, Madagascar, Asia, New Caledonia and Australia. Using a Bayesian molecular clock approach we estimated the separation of Iberotrechodes n. gen . and its sister clade to have occurred in the early Paleocene, at ca. 61 Ma. The biogeographic implications of this discovery are discussed in the context of the unusual abundance of phylogenetically and geographically isolated species of subterranean Carabidae in the Iberian peninsula. Finally, new phylogenetic relationships are highlighted within Trechodina, such as the sister-group relationship between the genera Pachytrechodes (Tanzania) and Himalotrechodes (Nepal), and the African origin of the genus Amblystogenium (Crozet Islands).